Pengembangan Kesejahteraan Anggota Melalui Implementasi Strategi Manajemen Pendidikan Bisnis di Outlet Ngunut Community (ONC) Tulungagung - Muh Ibnu Sholeh; Sevia Umi Wardini; Ulvia Fatkurin Fuad; Fakhruddin Al Farisy; Sutrisno Sutrisno; M. Zaki Maulana (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This community service program is carried out in the Ngunut area, Tulungagung Regency, with activity partner ONC. The problems faced include economic growth and technological developments emphasizing the need for ONC to remain competitive and sustainable. Tight competition in the local market, the need for updated technological knowledge, and business sustainability challenges are the main focus. Solutions carried out through the latest training provide a solid foundation for their self-development. Strategic collaboration with activity partners and analysis of new business opportunities are the foundation for developing business models that are not only innovative but also sustainable. Technology enablement and implementation of digital marketing strategies were key steps in improving ONC's operational efficiency and increasing their visibility in the tight local market. outreach on business sustainability provides better understanding for ONC members, helping them reduce environmental impacts and increase resource efficiency. As an integral part of this program, monitoring and evaluation are carried out strictly to measure the impact of each step taken. Thus, the community service program not only provides an immediate solution to the challenges ONC faces, but also forms the basis for long-term investment, supporting the growth and sustainability of their business in the future.